PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN IPAS DI SDN No. 49/VI Sei Hitam I, Koto Renah. - sulha, anis; ma'ashum (Program Studi Pendidikan Vokasi Seni Kuliner, 2025)
The problem faced in learning Natural and Social Sciences (IPAS) is the low learning outcomes of students due to conventional learning that does not involve students actively. This study aims to improve student learning outcomes through the application of the Problem Based Learning (PBL) learning model using the Classroom Action Research (CAR) method. The study was conducted in four stages: planning, implementation, observation, and reflection. The results of the study showed that the application of PBL effectively improved student learning outcomes in cognitive, affective, and psychomotor aspects. Students became more active in group discussions, were able to analyze problems, and showed a deeper understanding of the material Plants: Source of Life on Earth. In addition, this learning also improved students' collaboration and critical thinking skills. Although there were obstacles such as student readiness and limited resources, continuous reflection provided opportunities for improvement in the next cycle. Thus, PBL can be an alternative learning model that is relevant to improving the quality of education in elementary schools.